Produção de produtos florestais não madeireiros na Região Norte do Brasil período 2008 - 2017 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Non-timber forest products include all non-wood forest products, such as leaves, fruits, fibers, straws, seeds, oils, resins, gums, rubbers, medicinal plants, mushrooms, among others. The present work aimed to evaluate the production of non-timber forest products in the Northern region, from 2008 to 2017. Data collection was performed through the IBGE Automatic Recovery System - SIDRA. To choose the products to be analyzed, the production volume and its socioeconomic importance for the extractivist were considered. Nine products were selected, classified as food, oilseeds and fibers. Acai and Brazil nuts are the most important products for northern Brazil. Cumaru and copaíba oil showed an increase in the average price while piaçava presented a reduction in supply and market price during the period. It can be said that non-timber forest products in the northern region are being a subsistence form for the community of the Amazon, besides promoting the conservation of the forest.
Keywords: Extrativismo; Produção Florestal; Amazônia; CNPQ:: ENGENHARIAS